Membangun Website Menggunakan Framework CodeIgniter di STMIK YMI Tegal - Nadya Safitri; Mardi Yudhi Putra; Rita Wahyuni Arifin; Rayhan Wahyudin Ratu Lolly; Ahmad Safei (Jurnal SOLMA, 2021)
Background: The development of websites in various fields is increasing. One of the reasons is that it can facilitate access to the information needed without any limitations of space and time, and there is the ease in its management. This training is expected to increase the mastery and ability of students in building a website by using a framework, especially CodeIgniter. STMIK YMI Tegal is one of the partners who work together on this training with 62 (sixty-two) participants. This training is carried out by providing materials and demonstrations to participants in using the website using the CodeIgniter framework with the support of online media in the form of zoom, youtube, and google drive links. The training results carried out can be seen from the level of student acceptance of the material provided. This training received feedback, including the material presented by the resource persons, received a very good response with a score of 62.9%, and the suitability of the material to the needs of students received a very good response with a value of 53.2%. The sustainability of this activity is expected to have advanced training. Based on the results of this training, this training can provide benefits and mastery of participants in building a website, especially using the codeigniter framework currently needed by the industrial world.